2001
DOI: 10.1128/jb.183.19.5535-5543.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nested Deletions of the SRL Pathogenicity Island of Shigella flexneri 2a

Abstract: In this study, we determined the boundaries of a 99-kb deletable element of Shigella flexneri 2a strain YSH6000. The element, designated the multiple-antibiotic resistance deletable element (MRDE), had recently been found to contain a 66-kb pathogenicity island (PAI)-like element (designated the SRL PAI) which carries the Shigella resistance locus (SRL), encoding resistance determinants to streptomycin, ampicillin, chloramphenicol, and tetracycline. The YSH6000 MRDE was found to be flanked by two identical IS9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
69
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 46 publications
(48 reference statements)
9
69
0
2
Order By: Relevance
“…PAI-negative cells appear in the REPEC strain 84/110-1 and in S. flexneri 2a with frequencies of around 10 Ϫ6 to 10 Ϫ5 , which are comparable to previously obtained data for PAI I 536 and PAI II 536 (43,44). Other PAIs, like the Vibrio cholerae PAI or the Staphylococcus aureus PAI (S. aureus PAI 1), have not only the tendency to be deleted from the chromosome but both are also transmissible to recipient organisms by transducing phages (25,32,39).…”
Section: Vol 186 2004supporting
confidence: 80%
See 3 more Smart Citations
“…PAI-negative cells appear in the REPEC strain 84/110-1 and in S. flexneri 2a with frequencies of around 10 Ϫ6 to 10 Ϫ5 , which are comparable to previously obtained data for PAI I 536 and PAI II 536 (43,44). Other PAIs, like the Vibrio cholerae PAI or the Staphylococcus aureus PAI (S. aureus PAI 1), have not only the tendency to be deleted from the chromosome but both are also transmissible to recipient organisms by transducing phages (25,32,39).…”
Section: Vol 186 2004supporting
confidence: 80%
“…The deletion rates of 10 Ϫ6 to 10 Ϫ5 that were obtained for PAI I 536 to PAI V 536 were similar to the rates previously reported for other PAIs (34,43,44). With the exception of PAI III 536 , where a second deletion mechanism based on homologous recombination between a complete and a truncated IS100 copy was detected, excision and subsequent deletion of PAIs in E. coli 536 is mediated by site-specific recombination between short flanking DR sequences.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Genome sequencing of a representative ST91 strain, 2002017, revealed that it gained 2 unique multidrug resistance (MDR) islands, i.e., the Shigella resistance locus (SRL) and Tn7 (9). The SRL, which was first identified in the Japanese S. flexneri 2a strain YSH6000, carries genes for resistance against streptomycin, ampicillin, chloramphenicol, and tetracycline and also carries an iron acquisition system (9,(15)(16)(17). The SRL in 2002017 carries an additional set of tetracycline resistance genes but does not contain the iron acquisition system present in YSH6000.…”
mentioning
confidence: 99%